Super Cereal Plus and the Well-Being of Children from 6 to 24 Months in the Context of El Salvador's Nutrition Transition - Perez Escamilla, Rafael; Carroll, Grace J.; Grajeda, Ruben; Gordillo-Tobar, Amparo E. (World Bank, Washington, DC, 2020)
El Salvador is in a nutrition transition. In the past 20 years, stunting rates have declined by 25 percent in young children, while overweight and obesity have reached epidemic proportions, affecting about 60 percent of reproductive-age (15 to 49 years) women and increasing among children under five. To accelerate the progress in reducing stunting, anemia, and other micronutrient deficiencies, the government launched several interventions over the last three decades. This included mandatory fortification of staple foods, distribution of micronutrient supplements to all children, and distribution of fortified-blended foods (FBFs) in most municipalities. The implementation of programs such as these should be considered only after an analysis has been made of the target population’s nutritional needs; the context surrounding the program; and the availability, affordability, effectiveness, and acceptability of the intervention (de Pee and Bloem 2009; PAHO 2003). The aim of this paper is to discuss the effect and potential risks of distributing Super Cereal Plus (SC+) to the general population of children under two in the current epidemiological context of El Salvador. Evidence is unclear about the impact of fortified-blended foods, such as SC+, in preventing stunting. In El Salvador, there are concerns about children’s energy intake being a contributing factor to obesity. Furthermore, the micronutrient intake of young children through the interventions mentioned above may be excessive and potentially harmful.